The effect of CEOs’ cultural heritage on US firms’ long term invesment - Liew, Doris Wan Yin (2018)
This paper investigates if a CEO’s cultural heritage in healthcare and technology firms from the US have an effect on economic decisions. We use Hofstede’s Long-Term Orientation (LTO) index to examine the relationship between CEO’s cultural long-term orientation and investment decisions, namely Research and Development (R&D) and capital expenditure. The data captures the observations of 1770 CEOs and other C-suite executives from 1980 to 2017. Overall, our results are in contrast to the commonly held view that a long-term oriented CEO is more likely to spend more on long-term investments. We find that CEO’s LTO has a negative but weak relationship with R&D and capital expenditure in both healthcare and technology firms.